Interoperable simulation for asymmetric threats in maritime scenarios: a case based on virtual simulation and intelligent agents. (1st January 2013) - Tremori, Alberto; Massei, Marina; Madeo, Francesca; Reverberi, Andrea
The research proposes an approach based on modelling and simulation (M&S) for asymmetric threats (i.e., piracy, terrorism etc.) in complex, maritime scenarios in order to support decision makers and trainers in operational and organisational procedures. Considering that coordination and communication are really critical to face asymmetric threats and that the port is a complex network involving several actors, authors underline the importance of simulation and describe a set of simulation models for supporting decision making and training to face asymmetric threats. This paper provides an overview on a combined approach using interoperable M&S and data fusion techniques to analyse complex scenarios involving asymmetric threats in marine environments, in particular coastal areas and harbours; use of intelligent agents as driver for computer generated forces (IA_CGF) is a critical element for modelling events where many entities interact simultaneously (i.e., commercial and nautical traffic around a port).